Integrating research, practice and knowledge: Calohee project as case study of civil engineering - Alfredo Soeiro (2018)
WMSCI 2018 - 22nd World Multi-Conference on Systemics, Cybernetics and Informatics, Proceedings Volume 3, 2018, Pages 66-70 22nd World Multi-Conference on Systemics, Cybernetics and Informatics, WMSCI 2018; Orlando; United States; 8 July 2018 through 11 July 2018; Code 140272